Development and psychometric evaluation of the Nursing Teacher Emotional Labor Scale - Hanbo Feng; Meng Zhang; Jun Zhang; Xiaohan Li (BMC Nursing)
Abstract Background Nursing teachers, as a group with high emotional labor, report heightened levels of negative emotions and burnout. Focusing on the emotional labor of nursing teachers is essential for improving their emotional well-being and job satisfaction. However, there is a lack of assessment tools specifically tailored to the emotional labor of nursing teachers. Therefore, this study aimed to develop a scale for assessing nursing teachers’ emotional labor and to examine its psychometric properties. Methods The Nursing Teacher Emotional Labor Scale was developed in three phases. First, the scale’s dimensions and items were formulated based on concept analysis, qualitative research and a review of existing literature, followed by expert evaluation and a pretest. The second phase involved item analysis and exploratory factor analysis to evaluate the items and explore the scale’s factor structure. The third phase included testing for reliability and validity. Reliability was determined by internal consistency and test-retest reliability. Content validity, criterion-related validity, convergent and discriminant validity were employed to evaluate the validity. Results The final version of the scale comprised 20 items across four dimensions. The I-CVI for all items ranged from 0.857 to 1.000, and the S-CVI was 0.993. Convergent and discriminant validity results indicated that the average variance extracted for each dimension exceeded 0.5, the composite reliability values surpassed 0.7, and the square root of the average variance extracted values was greater than their respective correlation coefficients. The principal component analysis identified four factors accounting for 70.962% of the total variance. The fit indices from the confirmatory factor analysis met the criteria. The scale demonstrated good internal consistency, with a Cronbach’s α coefficient of 0.907 and a test-retest reliability of 0.865. Conclusion The Nursing Teacher Emotional Labor Scale has satisfactory reliability and validity. It serves as an effective tool for nursing teachers to evaluate their emotional labor levels within the context of nursing education. Additionally, it offers a valuable metric for nursing education administrators to develop interventions aimed at enhancing the emotional well-being of teachers.